Mechanical Properties of Novel Reinforced Spray in Place Pipe Material With Potential Fully Structural Performance Application - Azimi, M. Amin; Matthews, John C.; Bagherpour, Asal; Alsadi, Alhossin; Kraft, John J.; Alam, Shaurav; Campos, Urso (Frontiers in Water, 2021)
Many utility owners in the United States are actively searching for new and innovative rehabilitation techniques to help them regain control and repair large tracts of their networks; moreover, traditional open cut replacement is too costly and slow to keep up with demand. Many trenchless techniques such as Spray-In-Place Pipe (SIPP) lining have been adopted by municipalities to renew their aging pipeline systems. The further development of SIPP linings could benefit the water community in the United States and around the world. SIPP lining could play a key role in controlling the future expected burden caused by the aging distribution networks. This study aimed to investigate the mechanical properties of a newly proposed reinforced spray in place pipe (SIPP) lining material that boasts structural characteristics. This material is a spray applied two component polyurethane high build coating. Three forms of sample were investigated during these tests: (1) No Fiber-Baseline (2) Rigid-with one layer of carbon fiber (3) Rigid - with two layers of carbon fiber. Three types of tests are performed: tensile, flexural, and hardness tests. This study included both experimental and Finite Element Analysis (FEA). Target mechanical properties of proposed material can be improved by using carbon fiber (CF) as reinforcement and based on the results of this study, the SIPP lining material with two layers of CF reinforcement has the highest value of 8,067 psi and 16,534 psi during the tensile and flexural test, respectively.